The Disability-Disease Pairing: A Critical Analysis - Guzmán Castillo, Francisco (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
Disease and disability are two concepts closely linked for a long time, so that the second seems to be merely a consequence of the first. Even today both realities are treated as if they were the same thing in many public contexts and legal documents. However, this link between disease and disability is not as unavoidable as is often implied. According to the approach outlined in this paper it comes to different realities that are interpreted as part of the same thing under the code of the medical gaze. This paper presents and critically analyzes the archaeological origin of the interpretation of the person with disabilities and chronically ill in the discourse called «medical rehabilitation». Under this paradigm is imposed on the person with disabilities the social mandate to rehabilitate and/or cure to, so, be reintegrated and contribute to society. Otherwise, will be doomed to exclusion.